Artificial Muscle: Carbon Nanotube Yarn‐Based Glucose Sensing Artificial Muscle (Small 15/2016). Issue 15 (April 2016) - Lee, Junghan; Ko, Sachan; Kwon, Cheong Hoon; Lima, Márcio D.; Baughman, Ray H.; Kim, Seon Jeong
Abstract : On page 2085, S. J. Kim and co‐workers introduce a reversibly rotatable and highly glucose‐sensitive carbon multiwalled nanotube (MWNT) yarn artificial muscle. This yarn is created using a boronic acid‐conjugated hyaluronic acid/cholesterol nanogel (HC‐BA NG) deposited on a two‐end‐tethered structural actuator. By exploiting the swelling/de‐swelling of HC‐BA NG, the MWNT yarn actuator shows a reversible torsional actuation with short response time and high sensitivity for monitoring changes in glucose concentration with 5–100 mM range. This actuator can be utilized for an implantable glucose monitoring sensor.